Valence framing effects on moral judgments: A meta-analysis - McDonald, Kelsey; Graves, Rose; Yin, Siyuan; Weese, Tara; Sinnott-Armstrong, Walter (Cognition, 2021)
Valence framing effects occur when participants make different choices or judgments depending on whether the options are described in terms of their positive outcomes (e.g. lives saved) or their negative outcomes (e.g. lives lost). When such framing effects occur in the domain of moral judgments, they have been taken to cast doubt on the reliability of moral judgments and raise questions about the extent to which these moral judgments are self-evident or justified in themselves. One important factor in this debate is the magnitude and variability of the extent to which differences in framing presentation impact moral judgments. Although moral framing effects have been studied by psychologists, the overall strength of these effects pooled across published studies is not yet known. Here we conducted a meta-analysis of 109 published articles (contributing a total of 146 unique experiments with 49,564 participants) involving valence framing effects on moral judgments and found a moderate effect (d = 0.50) among between-subjects designs as well as several moderator variables. While we find evidence for publication bias, statistically accounting for publication bias attenuates, but does not eliminate, this effect (d = 0.22). This suggests that the magnitude of valence framing effects on moral decisions is small, yet significant when accounting for publication bias.